2015
DOI: 10.1097/qco.0000000000000150
|View full text |Cite
|
Sign up to set email alerts
|

Skin and subcutaneous infections in south-east Asia

Abstract: The described spectrum of cutaneous infection in south-east Asia can be imported to other areas due to increases in worldwide travel. Clinicians from other parts of the world should be aware of the common presentations of these diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…multiple facial lesions after returning from an endemic region such as Thailand, Vietnam, and China. 2 A diffuse dermal infiltrate comprising of foamy histiocytes or multiple granulomata containing unicellular round-ovoid organisms highlighted by GMS or PAS stains 2,3 as our patient's case depicts, is consistent with cutaneous talaromycosis. The extracellular elongated cells with centrally located transverse septa highlighted by GMS stain is useful in distinguishing T. marneffei from histoplasma capsulatum infection.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…multiple facial lesions after returning from an endemic region such as Thailand, Vietnam, and China. 2 A diffuse dermal infiltrate comprising of foamy histiocytes or multiple granulomata containing unicellular round-ovoid organisms highlighted by GMS or PAS stains 2,3 as our patient's case depicts, is consistent with cutaneous talaromycosis. The extracellular elongated cells with centrally located transverse septa highlighted by GMS stain is useful in distinguishing T. marneffei from histoplasma capsulatum infection.…”
mentioning
confidence: 52%
“…5 Patients with disseminated talaromycosis as an AIDS-defining illness should also be commenced on antiretroviral therapy and secondary prophylaxis with oral itraconazole or voriconazole until the CD4 count is sustained at more than 100cells/µL. 2 This case illustrates the diagnostic dilemma faced by clinicians treating HIV-positive patients with non-healing cutaneous ulcers and highlights the importance of a detailed physical examination and an accurate patient travel history.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For cutaneous form of penicilliosis, itraconazole should be administered, whereas in the case of severe infections, the use of Amphotericin B deoxycholate followed by itraconazole is recommended. Voriconazole may serve as an alternative for both mild and severe cases [137].…”
Section: Penicillosismentioning
confidence: 99%
“…M. marinum is transmitted to the human body through wounds or skin abrasions; it primarily causes skin lesions at the cooler parts of the body, especially the extremities [2]. A study of nontuberculous mycobacterial (NTM) infections of the skin showed that 81.8% of NTM skin infections were caused by M. marinum, and most patients had hobbies related to fish and water [3]. M. marinum infection causes a red-to-violaceous plaque or nodules, usually in a sporotrichoid pattern, although extensive deep skin lesions may occur.…”
Section: Introductionmentioning
confidence: 99%